Предмет: Алгебра,
автор: бегемод20003
Пожаааалуйстааааааааааа
Приложения:
Ответы
Автор ответа:
0
(a-b)^2=a^2-2ab+b^2
(2sqrt3-3sqrt2)^2=12-12sqrt6+18
sqrt24(6-5sqrt6)=6sqrt24-5sqrt144
12-12sqrt6+18+6sqrt24-5sqrt144=12-12sqrt6+18+12sqrt6-60=-30
(2sqrt3-3sqrt2)^2=12-12sqrt6+18
sqrt24(6-5sqrt6)=6sqrt24-5sqrt144
12-12sqrt6+18+6sqrt24-5sqrt144=12-12sqrt6+18+12sqrt6-60=-30
Похожие вопросы
Предмет: Математика,
автор: koumukami404
Предмет: Физика,
автор: starrpark195
Предмет: Английский язык,
автор: sekretnost57
Предмет: Математика,
автор: крис405
Предмет: Алгебра,
автор: lyanova1